Potensi Schotel Jakunre dengan Taste Andaliman Berbahan Pangan Lokal untuk Penderita Diabetes Mellitus: Potential of Schotel Jakunre with Andaliman Taste Made from Local Food Ingredients for Diabetes Mellitus Sufferers - Bernike Doloksaribu; Zuraidah Nasution; Ginta Siahaan; Rumida Rumida; Muhammad Atha Nugraha (Universitas Airlangga, 2025)
Background: In 2021, there were 19.5 million cases of diabetes mellitus, and it is predicted to rise to 28.6 million by 2045. Dietary modifications are necessary to prevent complications or the worsening of diabetes mellitus. An alternative can be using local food ingedients, rich in bioactive compounds and antioxidants, by combining food from job's tears, pumpkin that has been gound, with additional andaliman spices to enhance the flavor, called Schotel Jakunre. Objectives: Knowing the analysis of the physical and chemical quality of Jakunre Schotel as an alternative staple food for diabetes mellitus patients. Methods: The experimental research was conducted using a Completely Randomized Design (CRD) with 2 replications. The physical quality test of Schotel Jakunre products was carried out organoleptically, including texture, taste, aroma, and colour, also using a colour reader with a panel of 60 semi-trained participants. Analysis was done using ANOVA, followed by Duncan's test. The selected Schotel Jakunre formulation was tested for GI levels, total antioxidants, fiber, flavonoids, and zinc. Results: The acceptance test showed that treatment E, consisting of 300 g of jawawut flour, 100 g of pumpkin flour, and 100 g of small shrimp, was selected. Schotel Jakunre had a slightly brownish yellow colour, refreshing aroma, soft texture, and savory taste. Schotel Jakunre contained a GI of 61.52%, total antioxidants of 76.74 mg, fiber 6.67 g, flavonoids 7.75 mg, and zinc 0.3285 mg. Conclusions: Jakunre casserole with characteristics of slightly brownish yellow colour, soft texture and savory taste, as well as the fresh aroma typical of andaliman, contains high total antioxidants, fiber, flavonoids, and zinc. Additionally, it has a relatively low glycemic index, making the Jakunre casserole recommended for diabetes patients.